2020
DOI: 10.1038/s42255-020-00298-z
|View full text |Cite
|
Sign up to set email alerts
|

CD38 ecto-enzyme in immune cells is induced during aging and regulates NAD+ and NMN levels

Abstract: Decreased nicotinamide adenine dinucleotide (NAD + ) levels have been shown to contribute to metabolic dysfunction during aging. NAD + decline can be partially prevented by knockout of the enzyme CD38. However, it is not known how CD38 is regulated during aging, and how its ecto-enzymatic activity impacts NAD + homeostasis. Here we show that increases in CD38 in white adipose tissue (WAT) and liver during aging is mediated by accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
206
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(227 citation statements)
references
References 82 publications
7
206
0
Order By: Relevance
“…Researches have proved that the elevation of CD38 expression plays an inverse role in the regulation of nicotinamide adenine dinucleotide (NAD + ) and maintenance of NAD + homeostasis is critical for maintaining the normal function of the immune cells, such as cytotoxic (CD8+) T cells and macrophages [ 7 , 8 ]. CD38 possesses NAD + glycohydrolase activity and ADP ribosyl cyclase activity, both of which could convert NAD + to cADPR as well as hydrolase activity that converted cADPR to ADPR [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researches have proved that the elevation of CD38 expression plays an inverse role in the regulation of nicotinamide adenine dinucleotide (NAD + ) and maintenance of NAD + homeostasis is critical for maintaining the normal function of the immune cells, such as cytotoxic (CD8+) T cells and macrophages [ 7 , 8 ]. CD38 possesses NAD + glycohydrolase activity and ADP ribosyl cyclase activity, both of which could convert NAD + to cADPR as well as hydrolase activity that converted cADPR to ADPR [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SASP factors secreted from senescent cells such as senescent ECs can increase the expression of CD38 in non-senescent cells in vitro ( Chini et al, 2019 ). Recently, studies from two independent groups ( Chini et al, 2020 ; Covarrubias et al, 2020 ) revealed that CD38+ proinflammatory macrophages are the major cells that cause the decline of NAD+ levels in white adipose tissue and liver of mice. The expression of CD38 is induced in the proinflammatory macrophages through the SASP factors of senescent cells in vivo .…”
Section: Recent Advances In Cellular Senescencementioning
confidence: 99%
“…Recent studies showed that inflammation increases CD38-mediated NAD + degradation activity, which decreases NAD + . The increase in CD38 in metabolic tissues during aging is likely mediated by accumulation of pro-inflammatory M1-like macrophages that also express CD38 ( Chini et al, 2020 ; Covarrubias et al, 2020 ).…”
Section: Immunity Kyn Pathway Metabolites and De Novo Nad + Metabolismmentioning
confidence: 99%
“…Consequently, NAD + has a multifarious and highly important influence on cellular health, affecting an extensive suite of processes, including: DNA repair, central metabolism, circadian rhythms, meiosis and lifespan ( Imai and Guarente, 2014 ; Kato and Lin, 2014 ; Nikiforov et al, 2015 ; Chini et al, 2016 ; Yoshino et al, 2018 ; Okabe et al, 2019 ; Castro-Portuguez and Sutphin, 2020 ). Owing to its centrality in cellular homeostasis, defects in NAD + metabolism are often associated with a variety of disease states, seen in diabetes, neurological disorders, and various cancers ( Schwarcz et al, 2012 ; Imai and Guarente, 2014 ; Cantó et al, 2015 ; Garten et al, 2015 ; Nikiforov et al, 2015 ; Verdin, 2015 ; Cheng et al, 2016 ; Chini et al, 2016 ; Yang and Sauve, 2016 ; Williams et al, 2017 ; Liu et al, 2018 ; Poyan Mehr et al, 2018 ; Yaku et al, 2018 ; Yoshino et al, 2018 ; Okabe et al, 2019 ; Chini et al, 2020 ; Covarrubias et al, 2020 ; Katsyuba et al, 2020 ; Covarrubias et al, 2021 ). Administration of NAD + precursors such as nicotinamide mononucleotide (NMN), nicotinamide (NAM), nicotinic acid riboside (NaR), nicotinamide riboside (NR), and dihydronicotinamide riboside (NRH) has been shown to increase NAD + levels and ameliorate associated deficiencies in various model systems and in humans ( Belenky et al, 2007 ; Brown et al, 2014 ; Cantó et al, 2015 ; Edwards et al, 2015 ; Garten et al, 2015 ; Verdin, 2015 ; Chini et al, 2016 ; Lin et al, 2016 ; Ryu et al, 2016 ; Yang and Sauve, 2016 ; Zhang et al, 2016 ; Williams et al, 2017 ; Katsyuba et al, 2018 ; Liu et al, 2018 ; Meng et al, 2018 ; Mitchell et al, 2018 ; Poyan Mehr et al, 2018 ; Rajman et al, 2018 ; Yoshino et al, 2018 ; Sambeat et al, 2019 ; Vannini et al, 2019 ; ...…”
Section: Introductionmentioning
confidence: 99%